Mediators and mechanisms of heat shock protein 70 based cytoprotection in obstructive nephropathy - Mazzei, Luciana (Cell Stress Chaperones, 2015)
Urinary heat shock protein 70 (Hsp70) is rapidly increased in patients with clinical acute kidney injury, indicating that it constitutes a component of the endogenous stress response to renal injury. Moreover, experimental models have demonstrated that Hsp70 activation is associated with the cytoprotective actions of several drugs following obstruction, including nitric oxide (NO) donors, geranylgeranylacetone, vitamin D, and rosuvastatin. Discrete and synergistic effects of the biological activities of Hsp70 may explain its cytoprotective role in obstructive nephropathy. Basic studies point to a combination of effects including inhibition of apoptosis and inflammation, repair of damaged proteins, prevention of unfolded protein aggregation, targeting of damaged protein for degradation, and cytoskeletal stabilization as primary effectors of Hsp70 action. This review summarizes our understanding of how the biological actions of Hsp70 may affect renal cytoprotection in the context of obstructive injury. The potential of Hsp70 to be of central importance to the mechanism of action of various drugs that modify the genesis of experimental obstructive nephropathy is considered.